THE EFFECTS OF THE FRAMING OF NEGATIVE MESSAGES AND THE SOURCE’S CREDIBILITY TO ATTITUDES - Nailul Khikam; Jarot Prianggono (Fakultas Komunikasi, Sastra, dan Bahasa, 2022)
Covid-19 has significant social and economic impacts on society. The Indonesian National Police (Polri) as law enforcement officers have an important role to communicate the Covid-19’s health protocols to the public. The present study aims to analyze the effects of the framing of negative messages and the source’s credibility on the attitudes of Ngaliyan market’ traders. The present research is based on the message framing’s theory, source credibility’s theory and attitudes theory. The present study uses a quantitative approach by distributing a set of questionnaires to 100 Ngaliyan’s market traders. The results of present study show that the framing of negative messages’ variables have a positive and significant effect with a regression coefficient of 0.206. Similarly, the source credibility’s variable has a positive and significant effect with a regression coefficient of 0.467 on traders' attitudes with each degree of significance 0.05. The results show that the framing of negative messages can affect the participants’ attitudes positively.